(untitled) (Journal of the College of Basic Education, 2023)
A field experiment was conducted in the botanical garden of the Department of Life Sciences in the College of Education for SciencePure / Ibn Al-Haytham; University of Baghdad during the growing season (2012-2013) in order to study the effect ofIndustrial orange and lemon peel extracts at concentrations 10 and 9670 in growth and yieldbarley plant 70/8072 7074000700. The results showed a significant increase in plant height andNumber of leaves, number of prunings, leaf area, absolute growth rate, and growth rateRelative, area and weight of the flag paper, specific weight and specific area of the flag paper andThe length and density of the spike weight, the weight of the spike grain, the number and weight of the spikes, the length of the shaft, andYield index, grain yield density, grain weight, total plant weight, and weight0 seeds and migration coefficient for all treatments compared to control plants.